2015
DOI: 10.1016/j.ecotra.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Memory, expectation formation and scheduling choices

Abstract: Limited memory capacity, retrieval constraints and anchoring are central to expectation formation processes. We develop a model of adaptive expectations where individuals are able to store only a finite number of past experiences of a stochastic state variable. Retrieval of these experiences is probabilistic and subject to error. We apply the model to scheduling choices of commuters and demonstrate that memory constraints lead to sub-optimal choices. We analytically and numerically show how memory-based adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…This study aims to systematically compare estimated reliability ratios using self-reported (perceived or subjective) travel times from surveys and measured (actual or objective) travel times by GPS devices. Extending the literature on measurement errors (Brownstone and Valletta 1996;Fan, Guthrie, and Levinson 2016;Koster, Peer, and Dekker 2015;Levinson et al 2004;Li 2003;Parthasarathi, Levinson, and Hochmair 2013;Peer et al 2014;Varela, Börjesson, and Daly 2018; Varotto et al 2017;Vreeswijk et al 2014) we posit that these values are different and that perceived times will produce a higher reliability ratio than measured times.…”
Section: Research Question and Hypothesismentioning
confidence: 93%
“…This study aims to systematically compare estimated reliability ratios using self-reported (perceived or subjective) travel times from surveys and measured (actual or objective) travel times by GPS devices. Extending the literature on measurement errors (Brownstone and Valletta 1996;Fan, Guthrie, and Levinson 2016;Koster, Peer, and Dekker 2015;Levinson et al 2004;Li 2003;Parthasarathi, Levinson, and Hochmair 2013;Peer et al 2014;Varela, Börjesson, and Daly 2018; Varotto et al 2017;Vreeswijk et al 2014) we posit that these values are different and that perceived times will produce a higher reliability ratio than measured times.…”
Section: Research Question and Hypothesismentioning
confidence: 93%
“…Carlsson, 2010;Fayyaz et al, 2018), as well as to the limited literature that shows how constraints in mental processes may lead to biases in valuations (e.g. Koster et al, 2015).…”
Section: Introductionmentioning
confidence: 99%